79 Impact of COVID-19 wave 3 paediatric inpatient unit closures on transfers to tertiary care paediatric hospital. (21st October 2022) - Esser, Kayla; Badour, Bryn; Davis, Paul; Langrish, Kate; Chan, Pamela; Shouldice, Michelle; Beck, Carolyn; Van Clieaf, Judy; Baker, Andrew; Orkin, Julia
Abstract: Background: During Wave 3 of the COVID-19 pandemic, 15 community hospital paediatric inpatient units (comprising 167 beds) in Toronto were directed to close by the Greater Toronto Area (GTA) Hospital Incident Management System (IMS) Command Centre to increase adult inpatient bed capacity. All paediatric patients from closed inpatient units were redirected to a single tertiary care paediatric hospital, which increased capacity to accommodate these additional patients through activation of surge plans, while community hospitals redeployed resources to fill much needed gaps in adult care. Objectives: The objective was to describe patient characteristics of all transfers during the closure to explore the impact of community paediatric inpatient unit closures on transfers to the tertiary hospital. Design/Methods: A chart review of all transferred patients was conducted during the mandated closure and subsequent reopening. Transfers excluded ICU-level transfers as these were not impacted by IMS mandated closures. All transfers were categorized as requiring tertiary care (i.e. would typically be transferred) or not requiring tertiary care (i.e. only transferred due to the closure). Variables collected included sending hospital, admitting diagnosis, patient age, hospital disposition, and length of stay. Data was collected until the last paediatric unit reopened. Quality improvement project approval was granted by the institution. Results: A total of 858 patients were transferred to the tertiary hospital during the 67 day closure; of those, 530 were transferred solely to increase adult bed capacity (i.e. were categorized as patients requiring non-tertiary care). The majority of patients were admitted to general paediatrics (52%), and 39% went to a surgical inpatient unit. Most patients (68%) admitted had a length of stay between 24 and 72 hours. A third of patients admitted were under 2 years old, and a third were over 12 years old. The top three diagnoses for admission were infections, gastrointestinal issues, and general surgery. Two-thirds (60%) of transfers from closed sites came from three sites. Conclusion: More than half of the transfers occurred solely due to the mandated closures, and transfers returned to a stable volume once all sites re-opened. The GTA hospital system was able to respond to the mandated closure effectively through clear high-level communication, escalation processes and structures as well as responsive, real-time problem solving. Closures increased potential adult inpatient capacity by 6740 bed days and demonstrated an unprecedented system-wide approach to the provision of integrated paediatric care across the region.